2022
DOI: 10.1186/s12859-022-04909-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel six-gene prognostic signature based on colon adenocarcinoma immune-related genes

Abstract: Background Colon adenocarcinoma (COAD) is one of the most common gastrointestinal tumors worldwide, and immunotherapy is one of the most promising treatments for it. Identifying immune genes involved in the development and maintenance of cancer is key to the use of tumor immunotherapy. This study aimed to determine the prognostic value of immune genes in patients with COAD and to establish an immune-related gene signature. Differentially expressed genes, immune-related genes (DEIGs), and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A study showed that RTN3 functions as a new inhibitor and can activate the Chk2/p53 pathway to suppress hepatocellular carcinoma, which provides additional clues for a better understanding of the carcinogenic role of HBV [ 33 ]. Many other studies have shown that F2RL2 is a biomarker for a variety of tumors, such as colon adenocarcinoma and glioma [ 34 , 35 ]. In BC patients, F2RL2 is associated with the process by which metastatic BC spreads to bone [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that RTN3 functions as a new inhibitor and can activate the Chk2/p53 pathway to suppress hepatocellular carcinoma, which provides additional clues for a better understanding of the carcinogenic role of HBV [ 33 ]. Many other studies have shown that F2RL2 is a biomarker for a variety of tumors, such as colon adenocarcinoma and glioma [ 34 , 35 ]. In BC patients, F2RL2 is associated with the process by which metastatic BC spreads to bone [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection is one kind of common infection inducing immune. Immune—related genes have been applied to construct prognostic models for CC [ 12 ]. Our seven-gene bacterial response‐related prognostic model can accurately predict the OS of CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers preliminarily studied the predictive value of bacterial/microbiome-related genes in sepsis, anti-cancer drugs and cancers [5][6][7]. Metabolism, immune or cell death-related genes have been applied to construct prognostic models for CC or CRC [8][9][10][11][12], but bacterial response-related genes are rarely used as prognostic model to predict prognosis.…”
Section: Introductionmentioning
confidence: 99%